Individual Monitoring of Internal Exposure for Nuclear Medicine Workers in NINMAS through In-Vitro Bioassay Techniques (Bangladesh Journal of Nuclear Medicine, 2021)
Internal radiation monitoring of occupational radiation workers is essential for protecting them against the risks of incorporated radionuclides. More than 400 workers in Bangladesh are working with unsealed radioactive sources and most of them are employed at different nuclear facilities. Among the 18 Nuclear Medicine Centers in the country, the National Institute of Nuclear Medicine and Allied Science (NINMAS), Dhaka was selected for this study where workers get internal radiation exposure while processing and labeling of the liquid sources. The aim of this study was to estimate the activity concentration and committed effective doses from bioassay sample, namely urine samples of Nuclear Medicine (NM) workers due to handling of radioactive Iodine (131I), Technetium (99mTc) and Fluorine (F-18). Total 86 urine samples were collected from 17 occupational workers of NINMAS during the year 2017 and analyzed using High Purity Germanium (HPGe) detector. The radioactivity of 131I and (99mTc) was found 2.21±0.44 BqL-1 to 444 ± 39.91 BqL-1 and 5.53±1.12 BqL-1 to 603 ± 72.36 BqL-1 respectively. Due to low activity of the unsealed F-18 sources and for appropriate shielding, radioactivity of F-18 was found below the minimum detection level in the urine samples of the workers who handled it. The effective doses of occupational workers have also been calculated using the radioactivity concentration and the dose coefficients given in ICRP publication 78. The highest and lowest effective doses due to handling of the unsealed source of (99mTc) were 28.2 and 0.0258μSv for working with 780 and 36mCi of radionuclide respectively. On the other hand, the highest and lowest effective doses due to handling of 131I were 8.73and 0.045μSv, for working with 1425 and 55 mCi respectively. Both the doses are found to comply with ICRP annual dose limit of 20 mSv.Bangladesh J. Nuclear Med. 22(2): 125-129, Jul 2019